Strategi Pemasaran dan Pelayanan Produk Sisuka Dalam Meningkatkan Loyalitas Anggota Baitul Maal Wat Tamwil (BMT) - sulistyorini sulistyorini; Any Setyarini; Scorina Dwiantari (ITB AAS INDONESIA Surakarta, 2023)
Abstract SISUKA is a voluntary term deposit in the financing and fundraising industry and is the most dominant deposit in BMT Hudatama Semarang City. In carrying out one of its duties in providing funds from customer members, both on a small scale and on a large scale. Therefore, a strategy is needed to increase customer loyalty through marketing strategies and product service strategies. Research approach uses a qualitative approach by explaining or describing clearly and in detail a phenomenon and obtaining complete data about the subject of research. The method used in this study is comparative descriptive, namely by the way researchers describe the findings in the field from the results of interviews, observations and documentation. The subjects of this study are the Head of BMT Hudatama, employees of marketing, cashiers and CS as well as BMT Hudatama customers with certain secretaries. Data collection techniques in this study used data collection methods with observation, interviews and documentation. Data validation techniques use triangulation. The results of this study will report on the mechanism of SISUKA products (Voluntary Time Savings), marketing strategies through market segmentation, produc, price, promotion, and place as well as product services carried out through tangible, Emphaty, Reability, Responsivenes, Assurance. With a good mechanism, marketing strategy and good service will be able to increase customer interest in raising funds at BMT Hudatama so that customer loyalty increases.